Gender‐specific association of the interleukin 18 gene with symptomatic gallstone disease. Issue 4 (25th March 2013) - Shih, Shou‐Chuan; Yang, Horng‐Woei; Chang, Tzu‐Yang; Wang, Horng‐Yuan; Hu, Kuang‐Chun; Chang, Ching‐Wei; Chang, Chen‐Wang; Hung, Chien‐Yuan; Lin, Marie; Chan, Hui‐Wen; Lin, Wen‐Shan; Chang, Shih‐Chuan; et al.
Abstract Background and Aim Symptomatic gallstone disease (SGSD) induced several inflammatory responses and affected extrahepatic bile ducts. Although the pathology and environmental risk factors of gallstone disease are well documented, immune or inflammatory responses in SGSD development are still inconclusive. Interleukin 18 (IL18) is a pro‐inflammatory cytokine that plays an important role in immune, infectious, and inflammatory diseases because of the induction of interferon‐γ. In this study, we investigated whether polymorphisms of the IL18 gene were associated with SGSD susceptibility. Methods Genomic DNA was isolated from the whole blood samples of 445 patients with SGSD and 1121 gallstone‐free controls. The IL18 rs549908T>G, rs5744247C>G, rs187238G>C, rs1946518T>G, and rs360719A>G polymorphisms were genotyped using predeveloped TaqMan allelic discrimination assay. Results We found IL18 rs5744247G allele conferred protection against SGSD in female patients (odds ratio = 0.75, corrected P‐value = 0.015). Haplotype analysis revealed that TGGTA protected females from SGSD development (odds ratio = 0.75, corrected P‐value = 0.02). Conclusions Based on our findings, IL18 rs5744247C>G polymorphism could be a potential genetic marker to predict SGSD susceptibility in Han Chinese women.